NK Cells and Type 1 Diabetes - Melanie Rodacki; Adolpho Milech; José Egídio Paulo de Oliveira (Clinical and Developmental Immunology)
Type 1 diabetes (T1D) is characterized by an immuno-mediated progressive destruction of the pancreatic β cells. Due to the ability of NK cells to kill target cells as well as to interact with antigen-presenting and T cells, it has been suggested that they could be involved in one or multiple steps of the immune-mediated attack that leads to T1D. Abnormalities in the frequency and activity of NK cells have been described both in animal models and patients with T1D. Some of these alterations are linked to its onset while others seem to be a consequence of the disease. Here, we discuss the main characteristics of NK cells and review the studies that investigated the role of NK cells in T1D, both in mouse models and humans.